The Influence of Human Capital, Service Leadership on MSME Performance - Adriana Madya Marampa; Dian Intan Tangkeallo (Dinasti Publisher, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the productive businesses that are developing and have an important role in improving the economy both at the regional level and the economy of a country. This research method uses qualitative methods. The population in this research is Toraja MSMEs. The sample in this study was 144. The method of collecting data was by using a questionnaire using purposive random sampling. The research results show that there is a positive relationship between Human Capital and MSME Performance and Service Leadership on MSME Performance. The novelty in this research is by adding dimensions to servant leadership that are relevant to MSMEs, especially in Tana Toraja. In this case, the nature of the family culture experienced by workers can be considered in improving the performance of MSMEs, the nature of family will be measured by indicators of close relationships, trust and support, and communication. openness, a sense of shared ownership, healthy conflict resolution.